Genome-Wide Analysis of PEBP Genes in Dendrobium huoshanense: Unveiling the Antagonistic Functions of FT/TFL1 in Flowering Time - Song, Cheng; Li, Guohui; Dai, Jun; Deng, Hui (Frontiers in Genetics, 2021)
Dendrobium is a semi-shade epiphytic Orchidaceae herb with important ornamental and medicinal value. Parts of the cultivation of Dendrobium germplasm resources, as well as the identification of medicinal components are more studied, but the functional characterization of the flowering regulation in Dendrobium plants is less reported. Here, six PEBP family genes (DhFT3, DhFT1, DhMFT, DhTFL1b, DhFT2, DhTFL1a) were identified from Dendrobium huoshanense genome. The chromosomal level mapping showed that these genes were sequentially distributed on chromosomes 6, 9, 15 and 17. The paralogous gene DhTFL1b was corresponding to DhTFL1a that obtained by tandem duplication. The gene structure and conserved motif of DhPEBP indicated five PEBP genes apart from DhMFT contained four exons and three introns entirely. The phylogeny analysis showed that the PEBP gene family in A. thaliana, O. sativa, Z.mays, S. lycopersicum, and P. equestris were classified into three subclades—FT, TFL and MFT, which maintained a high homology with D. huoshanense. The conserved domain of the amino acid demonstrated that two highly conserved short motifs (DPDXP and GXHR) embed in DhPEBPs, which may contribute to the conformation of the ligand binding bag. The 86th position of DhFTs were tyrosine (Y), while 83th and 87th of DhTFL1s were histidine (H), suggesting they should have distinct functions in flowering regulation. The promoter of six DhPEBPs contained several cis-elements related to hormone induction, light response and abiotic stress, which indicated they could be regulated by the environmental stress and endogenous signaling pathways. The qRT-PCR analysis of DhPEBPs in short-term days induced by GA indicated the gene expressions of all DhFTs were gradually increased, whereas the expression of DhTFL1 was decreased. The results implied that DhPEBPs have various regulatory functions in modulating flowering, which will provide a scientific reference for the flowering regulation of Dendrobium plants.